A Good Example of Peaceful Coexistence? : The Soviet Union, Austria, and Neutrality, 1955-1991 - Mueller, Wolfgang (Verlag der Österreichischen Akademie der Wissenschaften)
This monograph, based on newly declassified sources from Western and Russian archives as well as on communist texts about international law and neutrality, is the first English-language account of Soviet policy towards neutral yet capitalist Austria during the Cold War. In order to make neutrality a model for the West, the Kremlin presented the unique Soviet-Austrian relationship as "a good example of peaceful coexistence" and a showcase for the benefits a Western state might reap by declaring neutrality. This honor, however, had strings attached: The communist doctrine of neutrality contained obligations that were expected to make it possible to exploit neutral states as instruments of Soviet policy and bring them nearer the socialist bloc.
Knowledge Unlatched
English
Keywords: History; Austria; European Economic Community; Moscow; Neutral country; Soviet Union; Vienna